Crisis at Go First – India's Low-Cost Airline - Rao G N, Raghavendra; R, Harish (2023)
On May 2, 2023, Go First, one of India’s top four domestic airlines, reported that it had suspended operations and filed for a voluntary insolvency resolution process with the National Company Law Tribunal (NCLT) due to lack of funds. The then CEO of Go First, Kaushik Khona, publicly accused Pratt & Whitney, the American engine supplier for most of the airline's planes, of causing the airline's difficulties. Over 50% of the airline's 57 aircraft had been grounded because Pratt & Whitney had failed to fix or replace the faulty engines before the warranted number of flying hours had passed. Pratt & Whitney, on the other hand, claimed that it was not obligated to replace or repair the engines since Go First owed it $100 million. Go First, in turn, claimed that it had lost Rs. 80,000 million (US$1 billion) due to the grounded planes and demanded compensation from Pratt & Whitney. Go First had approached the Singapore International Arbitration Centre (SIAC), which had ordered Pratt & Whitney to provide Go First with ten serviceable engines by April 27, 2023, and then 10 more each month until December 2023. Despite being ordered to do so, Pratt & Whitney did not comply with this, citing its previously stated position. Go First had been facing losses since 2019-20, primarily due to the COVID pandemic causing the halt of all flights and the rise in aviation turbine fuel costs. As a result, the airline owed Rs. 114,630 million (about US$ 1430 million) to banks, aircraft lessors, and various vendors, leading to its application for insolvency resolution. Thankfully, the National Company Law Tribunal (NCLT) accepted its application, allowing the airline a chance for possible revival and avoiding liquidation. Go First had been in operation for 17 years since 2006. NCLT's acceptance granted the airline immunity from creditors and aircraft lessors for at least six months, enabling it to negotiate debt restructuring and prepare for resuming operations. Simultaneously, Go First filed an emergency petition in the Delaware Federal court to enforce the arbitral award given by SIAC. The deliberations at NCLT went in favour of Go First, and in June 2023, the Committee of Creditors (i.e., the banks) gave in-principle approval to extend a loan of Rs. 4250 million (US$ 53 million) to Go First to help it recommence operations. However, the banks' Boards required a more robust rehabilitation proposal from Go First to operate profitably and repay outstanding loans. Overall, some positive developments had given hope that Go First would be able to resume operations soon. However, even if it did so, it would still face the challenge of regaining the market share lost to competitors. Many pilots and other employees had left for better opportunities elsewhere. It remained to be seen if the airline could overcome these challenges and operate profitably. Additionally, measures would need to be taken to prevent a similar situation from occurring again.